Effects of surgeon volume and hospital volume on clinical outcomes of breast cancer patients - Pavlushenko, Mariia; Liubota, Roman; Vereshchako, Roman; Anikusko, Mykola; Liubota, Iryna (Archive of Oncology, 2022)
cancer has become the leading cause of global cancer in the female population, ahead of lung cancer. Over the past half century, approach to the treatment of breast cancer has changed dramatically that led to improvement of survival rates and quality of life of patients. In particular, the changes affected the surgical treatment of breast cancer. The modern tactics of treating breast cancer patients has become more complex and requires a multidisciplinary approach led by an oncological surgeon. It requires the availability of specialized material and equipment in medical institutions and practical skills of surgeons that provide medical care to breast cancer patients. However, breast cancer patients may not receive the entire range of modern treatment options, due to limited capabilities of medical institution and/or surgeon that leads to deterioration in duration and quality of life of patients. The quality of medical care for breast cancer patients is directly proportional to the number of cases performed annually at a medical institution (hospital volume) or by a surgeon (surgeon volume). The results of this study can serve as a basis for further investigations of the relationship between the surgeon and hospital volume and other factors affecting the quality and diversity of medical care for breast cancer patients.